A kinetic inlet model for CFD simulation of large-scale bubble columns. (2nd February 2017) - Shi, Weibin; Yang, Ning; Yang, Xiaogang
Abstract: For the simulation of industrial-scale bubble column reactors, while modelling the gas distributor as uniform inlets oversimplifies the inhomogeneity introduced by inlets, the direct simulation of the full geometry of gas distributor or sparger brings about enormous pre-processing work and huge computational cost. A new inlet model is therefore proposed in this paper to simplify the modelling of gas distributor and meanwhile maintain the simulation accuracy. The new inlet model is validated by the comparison of the model prediction with experiments and the CFD simulation incorporating the full geometry of gas distributor for bubble columns of small or large diameters. Comparisons of three different inlet boundary conditions, i.e., the direct simulation of gas distributor, the uniform inlet, and the new inlet model, are made in the simulation of the total gas holdup, the radial profiles of gas holdup at different cross-sections along the column height, and the axial velocity of liquid at various superficial gas velocities. The results indicate that the new inlet model is capable of achieving a good balance between simulation accuracy and computational cost for the CFD simulation of large-scale bubble column reactors. Highlights: A kinetic inlet model to approximate the flow formed by gas distributor is proposed. The new kinetic inlet model is coupled with the DBS drag model. The constraint of employing fine mesh for modelling real holes has been removed. Cost-effective CFD simulation of large-scale bubble columns is achieved.